COMPARATIVE STUDY ON EVAPORATING DEMAND OF THE ATMOSPHERE USING ENERGY BALANCE METHODS (FUDMA JOURNAL OF SCIENCES, 2021)
In this study, two models are computed which are modified penman's monteith and Hargreaves – Samani model. The essence is to provide qualitative information related to the antagonistic effect of climate change on sustainable crop production through qualitative understanding of evaporation and transpiration processes in simple term evapotranspiration (ETo). This is computed using climatic parameters obtained from Abubakar Tafawa Balewa University; Agro weather station, Bauchi for the period of three years. This describes the two processes of water loss on plants, at first, through transpiration and on another note, on the soil surface by evaporation. The study deduced a comparative analysis on aforementioned Methods to determine the evaporating power of the atmosphere in improving crops yield and production through estimating the amount of water needed at the root zone of the plant and also, the seasonal variation during the study. The result of this study shows a little deviation in the two models. The model based on Modified Penman's Monteith displays optimal evapotranspiration. This makes the model satisfy its creation for estimation of reference evapotranspiration. In May, June, September, and October for 2013-2015, high trends are recorded. While In July and August low trend was recorded between climatic parameter and the estimated evapotranspiration. The statistical analyses also show that there is a linear relationship between the two estimated models. In the above months, it shows that application of water is needed for the healthy growth of crops and improved crops yield
Keywords: temperature; solar radiation; relative humidity; atmospheric pressure; evaporation; transpiration and crops production